The double intradermal test for tuberculosis in cattle, with reference to the "no lesion" re-actor,non-specific reactions and part played by saphrophytic acid-fast organisms in causing sensation to bovine and human tuberculin - Canham, A.S. (University of South Africa, 2014)
Typescript